2024
DOI: 10.1002/adhm.202304340
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 Immune Checkpoint Targeted Photoactivable Liposomes (iTPALs) Prime the Stroma of Pancreatic Tumors and Promote Self‐Delivery

Chanda Bhandari,
Azophi Moffat,
Nimit Shah
et al.

Abstract: Desmoplasia in pancreatic ductal adenocarcinoma (PDAC) limits the penetration and efficacy of therapies. We previously showed that photodynamic priming (PDP) using EGFR targeted photoactivable multi‐inhibitor liposomes remediates desmoplasia in PDAC and doubles overall survival. Here, we present bifunctional PD‐L1 immune checkpoint targeted photoactivable liposomes (iTPALs) that mediate both PDP and PD‐L1 blockade. iTPALs also improve phototoxicity in PDAC cells and induce immunogenic cell death. PDP using iTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…56,57 In addition to this, incorporating BPD in the NDs synthesis made the zeta potential even more negative, which was expected given that BPD nanoformulations are generally anionic in nature. 58,59…”
Section: Resultsmentioning
confidence: 99%
“…56,57 In addition to this, incorporating BPD in the NDs synthesis made the zeta potential even more negative, which was expected given that BPD nanoformulations are generally anionic in nature. 58,59…”
Section: Resultsmentioning
confidence: 99%
“…As previously described, anthracene-9,10-dipropionic acid (ADPA) was used as a colorimetric probe at 378 nm to detect singlet oxygen generation. 10 , 20 , 21 While the fluorescence changes in ADPA for singlet oxygen detection are more sensitive than the absorbance changes, absorbance was monitored as to avoid fluorescence artifacts arising from other factors such as contaminants or quenching. 37 It was found that ADPA decreased in absorbance at 378 nm for all samples ( Figure 4 A).…”
Section: Results and Discussionmentioning
confidence: 99%
“…For SOSG and HPF samples, fluorescence was measured with 460 nm excitation and 530 nm emission (bottom read, 100 gain, 20 μs integration time). ADPA was used as a colorimetric probe for singlet oxygen generation as previously described. ,, The absorbance of ADPA samples was measured at 378 nm (25 flashes, 0 ms settle time).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior work has demonstrated that lipid-anchoring of BPD markedly reduces its leakage from liposomes and enables codelivery of multiple agents. 14,15,18,27,28 In addition to local tumor ablation, PDT can also induce immunogenic cell death (ICD) through the release of damageassociated molecular patterns (DAMPs) such as calreticulin, heat shock protein (HSP) 60, HSP 70, and high mobility group box 1 (HMGB1). 29−31 A study by De Silva et al demonstrated the membrane translocation of ICD markers following PDT with a triple-receptor targeted liposomal formulation of BPD in an in vitro heterocellular 3D model of pancreatic tumors.…”
Section: ■ Introductionmentioning
confidence: 99%